Pengaruh Faktor Motivasi dan Kepercayaan terhadap Kinerja melalui Komitmen pada Manajer Proyek Kontruksi dengan Pendekatan Structural Equation Modeling - Sahadi, Sahadi; Wibowo, M. Agung (Department of Civil Engineering, Diponegoro University, 2013)
The aim of this research is to analyze the effects of motivation and trust on performance through the commitment of construction project managers by using Structural Equation Modeling (SEM) approach. The result of this research shows that motivation, trust, commitment, and performance are valid and reliable latent variables. Goodness of fit model resulted is fit, or the model is relevant to the data. Motivation and trust has positive effects on commitment and commitment has positive effects on performance.